معاشرتی اقدارکی ترویج میں عورت کی ذمہ داریاں---سیرت ازواج مطھرات کی روشنی میں عصری تجزیاتی مطالعہ: Resposibilities of women in promoting social values : An analytical conptemorary Study in the light of Sīrah azwāj e muṯaharāt - Dr.Fariha Anjum (jihat-ul-islam, 2023)
In Islam ,where worship and affairs have primary status, religious morals and social values are of key importance.Respect for social values is the basis of the rights that Allah has enjoined on the muslims.Prophet Muḥammad (saw)serve as a teacher of ethis and a bearer of good high moralities.A soiety is made up of both men and women.Allah has made some difference in physial structure and their psyhology,likewise Allah has devided the responsibilities and duties.A woman is responsible for family and social upbringing.According to Prophet Muḥammad (saw) every child is born with pure nature,then the training affets him.this training starts from a woman as mother and then the same woman continues to fulfill her responsibilities as wife,sister and a member of soiety. In this regard, the life of Azwāj muṯahrāt is a practical example beause they were trained by the Prophet muḥammad (saw) .In this article, the responsibilities of women in promotion of social values such as good behaviour,justice,truthfulness and charity will be discussed and social and moral aspect of the lives of Azwāj muṯaharāt will be highlighted.so that the today’s woman can fulfill her reponsibilities in best possible way and establish a better Islami society.